2014
DOI: 10.1002/pbc.24912
|View full text |Cite
|
Sign up to set email alerts
|

Camp programs for children with cancer and their families: Review of research progress over the past decade

Abstract: A systematic review was conducted of studies (2001-2013) about therapeutic recreation/camp for children with cancer and/or their family which measured either process or outcome variables qualitatively or quantitatively. Of 581 titles, 20 met the inclusion criteria. Research demonstrates positive impacts of camp on: cancer knowledge, mood, self-concept, empathy, and friendship, quality of life, and emotional well-being. This recent decade of research illuminates nuances in camp outcomes, which previously were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 31 publications
(60 reference statements)
2
40
0
Order By: Relevance
“…Specifically, campers reported high levels on the social and self-esteem subscales. This is consistent with the notion that chronic illness summer camps provide children with unique opportunities to socialize with peers who have similar health experiences and that summer camps provide children with experiences that build self-esteem (Brown, 2005; Martiniuk et al, 2014). Prior studies have demonstrated that children attending oncology camps report high levels of social support and that self-esteem improves pre to postcamp (Conrad & Altmaier, 2009; Packman et al, 2004).…”
Section: Summary and Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Specifically, campers reported high levels on the social and self-esteem subscales. This is consistent with the notion that chronic illness summer camps provide children with unique opportunities to socialize with peers who have similar health experiences and that summer camps provide children with experiences that build self-esteem (Brown, 2005; Martiniuk et al, 2014). Prior studies have demonstrated that children attending oncology camps report high levels of social support and that self-esteem improves pre to postcamp (Conrad & Altmaier, 2009; Packman et al, 2004).…”
Section: Summary and Discussionsupporting
confidence: 85%
“…In the context of such a community, campers may experience improvements in their self-efficacy, self-esteem, and independence. Camps also offer children and families respite from their cancer experience through recreation opportunities (e.g., outdoor activities, music and drama, arts and crafts) (Martiniuk, Silva, Amylon, & Barr, 2014). Together, the combination of social support through a camp community and camp activities is thought to positively impact campers’ physical, psychological, and social functioning (Martiniuk et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Camps increase interaction of youth with cancer and provide opportunities to share information and support. Literature reviews indicate that camp attendance is associated with improvements in self‐confidence, independence, and social contact . Individual studies evaluating camps are comprised primarily of nonrandomized, postcamp surveys, and interviews that highlight benefits, including camp is enjoyable, increased cancer knowledge through participation, diminished sense of isolation, and improved mood .…”
Section: Resultsmentioning
confidence: 99%